The Influence Of Protocoler Ethics On The Image Of Leaders In Banjarbaru - Irfan Irfan; Budi Kristanto (Dinasti Publisher, 2025)
Protocol ethics are an important aspect in government management that significantly influences the image of a leader. This study focuses on the Mayor of Banjarbaru and how protocol ethics contribute to public perception. The data shows that leaders who implement good protocol ethics tend to have a positive image in the eyes of the public. The research method used is qualitative with interviews, observations, and literature studies as data collection techniques. This study aims to identify the principles of protocol ethics and their impact on the image of the Mayor of Banjarbaru and provide recommendations for protocol practices in government.